Developing and Validating the Teacher Rating Scale of Learning Interest for Kindergarteners - Wu, Chung Chin (Frontiers in Psychology, 2022)
Studies have investigated learning interest based on either 2- or 4-factor theoretical framework. Empirical studies showed supportive evidence only toward 2-factor learning interest model, but it was primarily demonstrated above secondary level. It is unclear whether the dimensionality of learning interest of kindergarteners is consistent with those studies conducted above secondary level due to the absence of instrument for measuring kindergarteners’ learning interest. An effective and efficient learning interest scale was developed and validated for teachers’ use to rate kindergarteners to provide useful information for improving teaching and learning in practice. A total of 132 five years-old kindergarteners rated by 5 teachers in the formal study. Results clearly showed: (1) the developed teacher rating scale of learning interest was valid for understanding kindergartener’s learning interest and was equally suitable for boys and girls. (2) The 2-factor learning interest model was the best theoretical viewpoint for understanding kindergarteners’ learning interest across gender. Implications for learning interest research and practice are also discussed.